PERAN IBU RUMAH TANGGA DALAM PEREKONOMIAN KELUARGA STUDI KASUS DI DESA GUNEM KABUPATEN REMBANG - Dewi, Dian Ayu Liana (BBM (Buletin Bisnis & Manajemen), 2015)
The role of a housewife who works in this study has the objective to improve the economy of the family. The purpose of this study was to determine the contribution of the role of a housewife who works in general, are able to support their families, especially in Gunem village, subdistrict Gunem, Gunem district. The problem in this research is how the role of housewives in in Gunem village, subdistrict Gunem, Gunem district in helping the family economy, in the context of the daily needs of their families.The method used the qualitative description of the approach. In the process of data collection through direct observation, interviews with respondents and analyze existing data, both primary and secondary data. The results of this study indicate that women in general, housewives in particular has a strong role, morale high despite low income.Housewives who work can fill critical sectors role in the household. Such as education, health, economic and social. With the workings of a housewife, automatically becomes a double role, namely as a housewife and a female worker. That is where the role of housewife devoted to the family and the role of women who produce social interaction communication with parties outside the family. From the sociological aspect in this study the role and work of the spirit of the housewife in her efforts to help the welfare of thefamily is very high.